Plan de marketing para la comercialización de la producción agrícola de la Red Agroecológica de Loja - Rojas Paccha, Verónica Cristina (2023)
The objective of this research was to develop a marketing plan for the commercialization of the agricultural production of the Agroecological Network of Loja. Marketing strategies focused on market penetration were developed to increase the profitability of partners and strengthen the agroecological network. In addition, the descriptive exploratory method was used and on-site visits were made to the agroecological fair to find out the current state. On the other hand, the business philosophy was carried out with the corporate image of the Agroecological Network of Loja based on a survey and an interview to measure the participation of producers in the market, the services offered, and the communication and advertising policies. The results showed that the Loja Agroecological Network (RAL) does not have a business philosophy and lacks a marketing plan, therefore, a solid marketing proposal was developed with tactics and actions focused on digital marketing trends to achieve success in the commercial field. Keywords: Marketing plan, business philosophy, strategies, tactics.